A new Branch Sprung: Judas Scholarship in Gnostic Studies - Kim, David W. (Augustinianum, 2013)
The popularity of the Nag Hammadi texts has not been exhausted in the field of Gnostic studies over the last thirty years. The Gospels or Acts of female characters or marginalised male characters were the main sources scholars used to draw the picture of ancient dual mythology. The ongoing fascination with Coptic manuscripts gave birth to a new branch of scholarship in contemporary history when the Codex Tchacos was unveiled. Judas scholarship began in the middle of the last decade (2004-2006), even though it is claimed that the Codex Tchacos was unearthed in the 1970s. What kind of process did the ancient manuscript go through since its discovery? Where do readers stand with the new gospel? What is the future direction of Judas studies? This article not only chronologically discloses the ideas of individual scholars based on a field survey, but also argues that Judas studies can be developed beyond the general conclusion of second-century Sethian Gnosticism.